IMPLEMENTASI APLIKASI DIGITAL TIKTOK DALAM PEMBELAJARAN IPAS TOPIK SISTEM PENCERNAAN MANUSIA UNTUK MENUNTASKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Sahrul, Ageng; Ibrahim, Muslimin; Lutfauziah, Asmaul; Wahyudi, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of digital technology has encouraged teachers to integrate social media into learning activities. TikTok is one of the most popular digital platforms among elementary school students and has the potential to be utilized as an interactive learning medium. This study aimed to determine the effectiveness of implementing the TikTok digital application in science and social science (IPAS) learning on the topic of the human digestive system to improve students' learning outcomes. The research employed a quantitative approach using a pre-experimental One Group Pretest–Posttest Design. The participants consisted of 27 fifth-grade students at SDN Ngingas, Sidoarjo Regency. Data were collected through classroom observations, pretest-posttest assessments, and student response questionnaires. The collected data were analyzed descriptively using implementation percentage, N-Gain score, and student response percentage. The results indicated that the implementation of learning activities reached 100%, categorized as very good. Students' learning outcomes significantly improved with an average N-Gain score of 0.85, categorized as high. Furthermore, student responses toward the use of TikTok as a learning medium reached 96.30%, indicating a very positive response. These findings demonstrate that the TikTok digital application effectively enhances elementary students' learning outcomes and creates a more engaging, interactive, and meaningful learning environment in IPAS instruction. Keywords: Tiktok, Digital learning media, IPAS, Learning Outcomes, Elementary School